Vitamina A na alimentação do Pacu Piaractus mesopotamicus HOLMBERG, 1887 - Signor, Arcangelo Augusto (2011)
Two studies were carried out to evaluate vitamin A supplemented by retinyl acetate in pacu Piaractus mesopotamicus diets. In experiment I, 240 juveniles with an average initial weight of 17.55±3.22g were distributed randomized in 20 aquariums (500L), with five treatments and four replications. The vitamin A supplementation in diets was 0; 3.000; 6.000; 9.000 and 12.000 UI vitamin A/kg of diet supplemented by retinyl acetate (1.000.000 UI/g vitamin A), included in mineral and vitamin supplement. The juveniles were fed at 8:00; 11:00; 2:00 and 5:00, until apparent satiety. Effects of vitamin A supplementation in diets on productive performance was evaluated, as well as body yield, carcass chemical composition, hematologic and histologic variables of the liver. No difference was observed on feed conversion rate, survival, final length and factor condition for pacu fed with diets containing different levels of vitamin A. A quadratic effect was observed on parameters of final weight, daily weight gain, feed efficiency with better results for 6.666; 6.583 and 5.555 UI vitamin A/kg diet levels, respectively. There were no differences in carcass yield, carcass chemical composition, blood parameters and liver histology of pacu. In commercial diets formulated with ingredients for juveniles of pacu Piaractus mesopotamicus, reared in a recirculation system, it is recommended a supplementation of 5.555 UI vitamin A/kg diet, providing the best results in daily weight gain. For experiment II, 2.000 fish were used with initial average weight of 66.93±15.03 g and medium initial length of 14.59±1.07 cm, completely distributed at random in 20 cages of 5.0 m3 (five treatments and four replications with 20 fish/m3). The vitamin A supplementation in diets was by retinyl acetate (1.000.000 UI/g of vitamin A) included in mineral and vitamin supplement for diets presenting 0; 3.000, 6.000, 9.000 and 12.000 UI of vitamin A/kg of diet. The juveniles were fed at 8:30, 1:30 and 5:30 until apparent satiety. The effects of vitamin A supplementation in diets were evaluated on growth performance, body yield, carcass chemical composition, hematologic variables, vitamin A concentration and lipids in liver. No influence was observed on diet in vitamin A levels on growth performance in carcass yield, carcass chemical composition, blood parameters and lipids, however there was observed a higher concentration of vitamin A in liver. The vitamin A supplementation in diets for pacu juveniles reared in cages did not influence on growth performance, carcass yield, carcass chemical composition, blood parameters and liver lipids, however, there are influences in the vitamin A retention on the liver of fish.